The Punta de la Mona Rhodolith Bed: Shallow-Water Mediterranean Rhodoliths (Almuñecar, Granada, Southern Spain) - Del Río, Jesús; Ramos, Dino Angelo; Sánchez-Tocino, Luis; Peñas, Julio; Braga, Juan Carlos (Frontiers in Earth Science, 2022)
Shallow-water rhodolith beds are rare in the Mediterranean Sea and generally poorly known. The Punta de la Mona rhodolith bed extends for 16,000 square meters in shallow and oligotrophic waters at the southern coast of Spain, off Almuñecar in the Alborán Sea. Here, we present a detailed analysis of the structure (rhodolith cover and density, rhodolith size and shape, sediment granulometry) and morphospecies composition of the bed along a depth gradient. A stratified sampling was carried out at six depths (9, 12, 15, 18, 21, and 24 m), estimating rhodolith cover and abundance; rhodoliths were collected from one 30 by 30 cm quadrat for each transect, resulting in 18 samples and a total of 656 rhodoliths. The collected rhodoliths were measured and the coralline algal components identified morphoanatomically through a stereomicroscope and SEM. Sediment on the seafloor mainly consists of pebbles and cobbles; the highest rhodolith cover occurs between 15 and 18 m, and the lowest at the shallowest and deepest transects (9 and 24 m). Rhodolith size is similar throughout the depth range (23-35 mm) with a slight increase at 24 m, although the largest rhodoliths occur at 21 m. In monospecific rhodoliths, size depends more on the forming species than on depth. We found 25 non-geniculate coralline morphospecies, nearly all rhodolith-forming morphospecies reported in the Mediterranean Sea in recent accounts. The highest morphospecies richness (18-19) and proportional abundance were found at intermediate depths (15-18 m), where rhodolith cover is also highest. Lithophyllum incrustans and Lithophyllum dentatum dominate at shallow depths (9-12 m), whereas Lithothamnion valens is the dominant species at intermediate and greater depths. Overall, the latter species is the most common in the rhodolith bed. The shallow-water rhodolith bed in Punta de la Mona is probably the most diverse in the Mediterranean Sea. This highlights the importance of the conservation of this habitat and, in general, emphasizes the role of the Alborán Sea as a diversity center of coralline algae. The Punta de la Mona example opposes the common assumption in the geological literature that rhodolith beds are indicative of oligophotic environments with high nutrients levels.